A case of early diagnosis of congenital multisystem langerhans cell histiocytosis with thymic involvement triggered by newborn screening - Yoji Uejima; Masayuki Iijima; Koichi Oshima; Ken Kawabata; Akihisa Nitta; Taiki Sato; Yoko Sato; Zenshiro Tamaki; Takahiro Hosokawa; Masaki Shimizu; Katsuyoshi Koh; Atsuko Nakazawa (Immunological Medicine)
T-cell receptor excision circle (TREC)-based newborn screening is a method for the early detection of severe combined immunodeficiency (SCID); however, undetectable TREC level results have also been reported in conditions other than SCID. To date, no studies have investigated the dynamics of TREC levels in patients with Langerhans cell histiocytosis (LCH). Here, we report a case of congenital multisystem LCH with thymic involvement diagnosed following a negative TREC result obtained through newborn screening. Partial remission was achieved with chemotherapy, and TREC levels subsequently recovered. LCH involving the thymus should be considered among the differential diagnoses for negative TREC results.